Varieties of Health Care Devolution: 'Systems or Federacies'? - Joan Costa-Font; Laurie Perdikis (London School of Economics and Political Science (LSE), European Institute, 2018)
Some European countries have devolved health care services to subnational units. This is especially the case in unitary states that are organised as a national health service, where choice is not 'built into' the health care system. We argue that there are different models of devolving authority to subnational jurisdictions which have repercussions for regional health care inequalities and the amount of policy interdependence across regions. We examine broad trends in two institutional models of devolution: a 'federacy model', where only a few territories obtain health care responsibilities (such as in the United Kingdom), and a 'systems model', where the whole health system is devolved to a full set of subnational units (such as in Spain). This paper briefly discusses the impact of these two models of devolution on the regional diversity of the health system. Our findings suggest that a 'systems model' of decentralisation, unlike a 'federacy model', gives rise to significant policy interdependence. Another finding indicates that geographical dispersion of health care activity is larger in the 'federacy model'.
Keywords: 330; regional dispersion; models of devolution; federacy; policy interdependence; systems model; Spain; UK